Pemanfaatan Smartphone Dalam Pembelajaran Matematika (Persepsi Mahhasiswa Universitas Nurul Jadid Prodi Pendidikan Matematika) - Ika Rizqiyanti; Jauharotul Maknunah (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2025)
A smartphone is a smart phone that has advanced features with high capabilities similar to a computer, a device that allows for communication as well as PDA (Personal Digital Assistant) functions and computer-like capabilities. The use of smartphones from year to year is increasing. Smartphones are owned by all students of the mathematics education study programme at Nurul Jadid Paiton University. Good use of smartphones will help students in lectures and vice versa, bad use will have a negative impact on students. The purpose of writing this article is to find out how the perceptions of mathematics education study programme students at Nurul Jadid University Paiton towards the use of smartphones in lectures. This research is quantitative research with descriptive data analysis using survey method. The student perception questionnaire was used as an instrument to collect data on the perceptions of mathematics education study programme students who took the Mathematical Statistics course in the February-July 2025 semester. The results of the study were 52% of students had a good perception, 31% were very good and 16.3% were not good at the use (positive impact) of smartphones in supporting lectures while for student perceptions of the negative impact of smartphones on lectures were 41.64% agreed and 9.42% strongly agreed and those who disagreed and strongly disagreed were 48.94%. With the good perception of the use of smartphones in class, it is expected to be able to provide alternative learning tools that support the process of improving student learning achievement.